The impact of a self-management educational program coordinated through WhatsApp on diabetes control - Muaed Al Omar; Sanah Hasan; Subish Palaian; Shrouq Mahameed (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Background: Social media can effectively mediate digital health interventions and thus, overcome barriers associated with face-to-face interaction. Objective: To assess the impact of patient-centered diabetes education program administered through WhatsApp on glycosylated hemoglobin (HbA1c) values, assess the correlation, if any, between health literacy and numeracy on intervention outcomes Methods: During an 'intervention phase' spread over six months, target diabetic patients (N=109) received structured education through WhatsApp as per the American Association of Diabetes Educators Self-Care Behaviors recommendations. The control group with an equal number of participants received 'usual care' provided by health professionals void of the social media intervention. Changes in HbA1c levels were recorded thrice (at baseline, 3 and 6 months) for the test group and twice (baseline and 6 months) for the control group. Change in HbA1c values were compared and statistical significance was defined at p<0.05. Baseline health literacy and diabetes numeracy were assessed for both groups (N=218) using the Literacy Assessment for Diabetes (LAD), and the Diabetes Numeracy Test (DNT), respectively, and values were correlated with HbA1c change p<0.05. Participants' satisfaction with the intervention was also assessed. Results: The average age of respondents was 41.98 (SD 15.05) years, with a diabetes history of 10.2 (SD 8.5) years. At baseline, the average HbA1c in the control and test groups were 8.4 (SD 1.06) and 8.5 (SD 1.29), respectively. After six months, a significant drop in HbA1c value was noticed in intervention group (7.7; SD 1.35; p= 0.001); with no significance in the control group (8.4; SD 1.32; p=0.032, paired t-test). Moreover, the reduction in HbA1c was more in the test group (0.7%) than the control group (0.1%) with a difference of 0.6% which is considered clinically significant. There was no significant correlation between LAD score and HbA1c at baseline (r=-0.203, p=0.064), 3 months (r=-0.123, p=0.266) and 6 months (r=-0.106, p= 0.337) Pearson correlation. A similar result was observed with DNT, where DNT score and HbA1c at baseline, 3 months and 6 months showed no correlation (r=0.112, 0.959 and 0.886; respectively) with HbA1c levels. Eighty percent of the respondents found the social media intervention 'beneficial' and suggested it be used long term. Conclusions: Diabetes education via WhatsApp showed promising outcomes regardless of the level of patients' health literacy or numeracy.